Induction of PrPSc-specific systemic and mucosal immune responses in white-tailed deer with an oral vaccine for chronic wasting disease. Issue 5 (3rd September 2017) - Taschuk, Ryan; Scruten, Erin; Woodbury, Murray; Cashman, Neil; Potter, Andrew; Griebel, Philip; Tikoo, Suresh K.; Napper, Scott
ABSTRACT: The ongoing epidemic of chronic wasting disease (CWD) within cervid populations indicates the need for novel approaches for disease management. A vaccine that either reduces susceptibility to infection or reduces shedding of prions by infected animals, or a combination of both, could be of benefit for disease control. The development of such a vaccine is challenged by the unique nature of prion diseases and the requirement for formulation and delivery in an oral format for application in wildlife settings. To address the unique nature of prions, our group targets epitopes, termed disease specific epitopes (DSEs), whose exposure for antibody binding depends on disease-associated misfolding of PrP C into PrP Sc . Here, a DSE corresponding to the rigid loop (RL) region, which was immunogenic following parenteral vaccination, was translated into an oral vaccine. This vaccine consists of a replication-incompetent human adenovirus expressing a truncated rabies glycoprotein G recombinant fusion with the RL epitope (hAd5:tgG-RL). Oral immunization of white-tailed deer with hAd5:tgG-RL induced PrP Sc -specific systemic and mucosal antibody responses with an encouraging safety profile in terms of no adverse health effects nor prolonged vector shedding. By building upon proven strategies of formulation for wildlife vaccines, these efforts generate a particular PrP Sc -specific oral vaccine for CWD as well as providing a versatile platform, in terms of carrier protein and biological vector, for generation of other oral, peptide-based CWD vaccines.